Novel scorpion type phthalocyanine chemosensors for detection of selective-metal ion by inducing H- and J-aggregations in solution; synthesis, characterization and electrochemistry - KOCA, ATIF (ELSEVIER SCI LTD, 2014)
Scorpion type metal(II) and metal(III) phthalocyanine reversible sensors, MPc[beta-[dihydroxypropylthio](8)]X [where M = 2H(2), Cu(II)(3), Co(II)(4), Mn(III)(5) or Pb(II)(6); X = Cl only when M = Mn(III)] have been prepared for detection of selective soft metal ion from the corresponding metal salts and 4,5-bis-(1,2-dihydroxy propylthio)-phthalonitrile compound (1). Upon addition of Ag(I), Pd(II), Zn(II), Ni(II), Na(I) and Mg(II) metal ions into the solution of 2, 3, 4 or 6 in THF, only Pd(II) and Ag(I) metal ions result in particular responses pronounced in the Q- and the B-bands of their UV-Vis spectra as a result of donor acceptor interactions. The novel compounds have been characterized by using MALDI-TOF MS, FT-IR, UV-Vis, H-1 NMR,C-13 NMR, AFM and elemental analysis. In compounds (4) and (5), metal based electron transfer reactions have been observed in addition to the common phthalocyanine ring-based electron transfer processes. In case of compound (6), stable anionic species have been observed without demetallation of the Pb(II). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Chemosensor; Spectroscopy; Silver and palladium; H- and J-aggregation; Electrochemistry; IN-SITU SPECTROELECTROCHEMISTRY; ZINC PHTHALOCYANINES; MANGANESE PHTHALOCYANINE; ELECTROCATALYTIC ACTIVITY; LEAD PHTHALOCYANINE; HYDROGEN-PRODUCTION; THIN-FILMS; COBALT; IRON; SPECTROSCOPY